The Effect of Lavender Aroma Complementary Therapy on Insomnia in the Elderly at Joyah Uken Takengon Nursing Home - Masdalifah Pasaribu (Science Midwifery, 2020)
Insomnia is a symptom experienced by clients when they have difficulty falling asleep, wake up frequently at night, and wake up too early in the morning. Treatment of insomnia in the elderly can be done pharmacologically and non pharmacologically. One type of non-pharmacological treatment for insomnia in the elderly is complementary lavender aroma therapy. Smelling lavender can make a person relax, making it easy for the elderly to fall asleep. This study aims to determine the effect of complementary lavender aroma therapy on insomnia in the elderly at the Joyah Uken Nursing Home, Central Aceh Regency. This research is a quasi-experimental type using the one group pretest and posttest design method. The population in this study were all elderly people over 60 years of age. The sample in this study used a total sampling technique of 14 elderly. The research instrument used a measuring tool for the study of biological psychiatry, the Jakarta insomnia rating scale, and using the observation sheet. Statistical analysis using paired t-test. The level of insomnia before being given complementary lavender aroma therapy in the elderly was mild 14.3%, moderate 50.0% and heavy 35.7%. The level of insomnia after being given complementary lavender aroma therapy decreased to 42.9% and moderate 57.1%. Hypothesis test results obtained sig value of 0.000 (<0.05). This shows that there is an effect of complementary lavender aroma therapy on insomnia. The conclusion is that there is an effect of complementary lavender aroma therapy on insomnia and it is suggested that lavender aroma therapy can be given as an effort to overcome and reduce insomnia levels in the elderly.